Vapor/liquid polymerization of ultraporous transparent and capacitive polypyrrole nanonets. Issue 25 (19th June 2019) - Santino, Luciano M.; Diao, Yifan; Yang, Haoru; Lu, Yang; Wang, Hongmin; Hwang, Erica; D'Arcy, Julio M.
Abstract : Polypyrrole nanonets exhibiting a high specific capacitance of 518 F g −1 are synthesized via vapor–liquid interfacial polymerization and engineered into electrochemical capacitors. Abstract : Freestanding, contiguous, and translucent polypyrrole nanonets are prepared within 90 minutes at room temperature in Petri dishes by exposing aqueous oxidant to static pyrrole vapor. The nanonets are 150 nm thick, with variable densities depending on polymerization time. The nanonets maintain a low sheet resistance of 29.1 Ω □ −1 at 30% optical transmission, and 423 Ω □ −1 at 50% transmission. A mechanism is proposed in which polypyrrole islands serve as nucleation sites for further surface-tension constrained polymerization. The nanonets exhibit a high degree of electrochemical dopability (over 24%). Nets are robust and processable, as evidenced by their ability to drape over 2D and 3D substrates. Large areas of films are manually twisted into highly porous sub-millimeter diameter conductive wires, able to recover their two-dimensional structure upon immersion in solvents. Moreover, nanonets exhibit a high specific capacitance of 518 F g −1 for a 1.2 V potential window. Electrochemical capacitors fabricated with nanonet active electrodes show a high energy density of 9.86 W h kg −1 at 1775 W kg −1 when charged to 0.8 V.